2021
DOI: 10.1155/2021/1077358
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Risk Factors of Hospital Emergency Nursing Based on Comprehensive Nursing Methods

Abstract: In order to improve the comprehensive nursing effect of the hospital emergency treatment, this paper analyzes the process of the hospital emergency treatment. In addition, this paper combines the possible risks to analyze the risk factors of the comprehensive nursing in the hospital emergency treatment and builds an intelligent analysis model based on the actual situation of the hospital emergency treatment. At the same time, this paper conducts a systematic survey of emergency services and gives the compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…One is the method using handcrafted features. Such methods often use artificial features to represent events, such as object trajectory features [7][8][9][10], spatiotemporal gradients [11][12][13], optical flow histograms [14][15][16][17], and dynamic blending textures [18][19][20][21]. After obtaining the features representing events in this type of method, the next step is to use common machine learning models such as support vector machines (SVM) and Gaussian process models to build anomaly detection models.…”
Section: Introductionmentioning
confidence: 99%
“…One is the method using handcrafted features. Such methods often use artificial features to represent events, such as object trajectory features [7][8][9][10], spatiotemporal gradients [11][12][13], optical flow histograms [14][15][16][17], and dynamic blending textures [18][19][20][21]. After obtaining the features representing events in this type of method, the next step is to use common machine learning models such as support vector machines (SVM) and Gaussian process models to build anomaly detection models.…”
Section: Introductionmentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Analysis of Risk Factors of Hospital Emergency Nursing Based on Comprehensive Nursing Methods” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled "Analysis of Risk Factors of Hospital Emergency Nursing Based on Comprehensive Nursing Methods" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%